2006
DOI: 10.1097/01.blo.0000224062.39990.48
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Complex Idiopathic Clubfoot

Abstract: Treatment with the Ponseti method corrects congenital idiopathic clubfeet in the majority of patients. However, some feet do not respond to the standard treatment protocol. We describe the characteristics and treatment results of these complex idiopathic clubfeet. We identified 50 patients (75 clubfeet) from 762 consecutive patients treated at five institutions. Clinically, complex clubfeet were defined as having rigid equinus, severe plantar flexion of all metatarsals, a deep crease above the heel, a transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
260
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(276 citation statements)
references
References 6 publications
8
260
0
8
Order By: Relevance
“…This was also reported by Haft et al [14] and Lehman et al [21]. Overall, we found that 20.7% of feet required TATT; this is similar to results by Ponseti et al [27], but the need for TATT was statistically lower in patients who followed the Ponseti brace protocol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was also reported by Haft et al [14] and Lehman et al [21]. Overall, we found that 20.7% of feet required TATT; this is similar to results by Ponseti et al [27], but the need for TATT was statistically lower in patients who followed the Ponseti brace protocol.…”
Section: Discussionsupporting
confidence: 91%
“…Possible reasons can include the feet either (1) not being fully corrected before being placed in a brace or (2) the development of a relapse despite brace wear making continued brace use impossible. Various authors have suggested modifying the brace to improve brace tolerance [5,15,22,27]. In our study, late presenters were more brace-tolerant.…”
Section: Discussionmentioning
confidence: 47%
“…Plaster casts were applied with careful molding and holding the talar neck while elevating the first ray and abducting the foot gradually. Long-leg casts were applied and changed every week [24]. Abduction did not always reach 70°, but there was enough abduction to get the feet plantigrade.…”
Section: Methodsmentioning
confidence: 99%
“…technique was described to treat difficult feet with substantial cavus, complex feet, resulting in fewer number of clubfeet undergoing posteromedial releases [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation